Associations Between the Small Hive Beetle and the Yeast Kodamaea ohmeri Throughout the Host Life Cycle - Amos, B. A.; Leemon, D. L.; Hayes, R. A.; Cribb, B. W.; Furlong, M. J.
The small hive beetle, Aethina tumida Murray (Coleoptera: Nitidulidae), is a pest of colonies of social bees, including the honeybee Apis mellifera L. (Hymenoptera: Apidae). We investigated A. tumida oviposition behavior and development and found that it laid eggs in clutches that ranged in size (3-75 eggs per clutch)and that when fed on hive products in laboratory culture (27°C; RH 65 per cent; 12:12 (L:D)h)it completed three larval instars before pupation. The yeast Kodamaea ohmeri (Etchells & Bell)Y. Yamada, T. Suzuki, M. Matsuda K. Mikata (Ascomycota: Saccharomycotina)is associated with A. tumida, but the exact nature of this relationship is unknown. We examined the association in host eggs, larvae, pupae, and adults to establish its extent and potential specificity and determined the likely mechanism of vertical transmission. K. ohmeri was detected in egg mucilage and on host cuticle and from internal preparations of A. tumida at every stage of development. Based on colony forming unit (CFU)counts, the K. ohmeri densities varied significantly between developmental stages; the highest internal density was recorded in third instar larvae. Presence of K. ohmeri within adult A. tumida was not affected by contamination of the cuticle by the yeast during the larval and pupal stages nor by the mated status of the adult. This deepened understanding of A. tumida ovipositional behavior and larval development along with a better understanding of the relationship between K. ohmeri and its host is important for the development of management strategies for this important pest.
Keywords: HONEYBEE; INSTAR; NITIDULIDAE; SYMBIOSIS; TRANSMISSION